980mpa grade low density steel and method of making same

CN117758139BActive Publication Date: 2026-10-09NORTHEASTERN UNIV CHINA +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311532593.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-17
Publication Date
2026-10-09
Estimated Expiration
2043-11-17

AI Technical Summary

Technical Problem

虽然轻量化原材料的使用能够降低汽车的总体重量,但存在成形工艺复杂、焊接性能较差、碰撞吸收能较低及格昂贵、产量较小等不足,限制了轻量化原材料的市场化应用

Benefits of technology

[0021] The 980MPa grade low-density steel provided by this invention reduces the density of the steel by adding the lightweight element Al, appropriately increases the Mn content to mitigate the adverse effects of Al addition on the shrinkage of the austenite phase region, and utilizes microalloying elements (Nb, V, Ti) to refine the grains and improve the product's strength and plasticity through precipitation. The preparation method utilizes a bell-type annealing furnace to perform a reverse phase transformation from martensite to austenite, improving the stamping effect; and by controlling the hot rolling and bell-type annealing processes, a thinner and denser oxide layer is obtained, avoiding environmental pollution caused by pickling, shot blasting, and other treatments. This invention requires low equipment investment and is highly operable, providing technical support for the development of pickling-free 980MPa grade low-density high-strength steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117758139B_ABST
    Figure CN117758139B_ABST
Patent Text Reader

Abstract

The application discloses a 980MPa-grade low-density steel, and chemical components are as follows in percentage by weight: C: 0.20%-0.45%, Si: 0.10-0.35%, Mn: 4.8%-7.2%, P: 0.015% or less, S: 0.008% or less, Al: 4.5%-5.5%, Nb: 0.015-0.035%, V: 0.030-0.070%, Ti: 0.015-0.065%, N: 0.004% or less, and the rest is Fe and inevitable impurities. The preparation method comprises smelting, hot rolling and cover annealing. The 980MPa-grade low-density steel provided by the application reduces the density of the steel by adding light element Al, appropriately increases the content of Mn element, reduces the adverse effect of the shrinkage of austenite phase area caused by the addition of Al element, utilizes micro-alloy elements Nb, V and Ti to refine grains and improve the strength and plasticity of the product. The thin and dense oxide layer is obtained by adjusting the hot rolling and cover annealing process, environmental pollution caused by pickling, shot blasting and other treatments is avoided, and technical support is provided for the development of the 980MPa-grade low-density steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of low-density high-strength steel technology, specifically to a 980MPa grade low-density steel and its preparation method. Background Technology

[0002] The automotive manufacturing industry is a pillar industry of the national economy. With the increasing prominence of energy shortages and environmental pollution, lightweighting has become a key focus for carbon emission reduction in the automotive sector. Currently, there are three main approaches to achieving automotive lightweighting: First, using lightweight raw materials such as aluminum alloys, magnesium alloys, and carbon fiber composites. While the use of lightweight raw materials can reduce the overall weight of a car, they suffer from drawbacks such as complex forming processes, poor welding performance, low impact energy absorption, high cost, and low production volume, limiting their market application. Second, using ultra-high-strength steel to replace traditional automotive steel, reducing steel sheet thickness to lighten the car. However, as steel sheet strength increases, forming capacity decreases, leading to problems such as cracking, wrinkling, and excessive springback. Furthermore, as steel sheet thickness decreases, the stiffness of some vehicle components is excessively reduced, and acoustic problems causing discomfort for passengers arise, limiting its widespread adoption. Third, developing a steel grade that combines high strength, high elongation, and low density. Low-density steel possesses excellent mechanical and physical properties and significant weight reduction effects, making it a hot research topic for the automotive industry and its suppliers.

[0003] Conventional hot-rolled products typically exhibit significant red iron oxide scale on their surface, reducing the processing utilization rate of components. During forming, the oxide layer is prone to uneven peeling, and the surface quality of components after electrophoretic painting does not meet requirements. Therefore, raw materials require pickling and shot blasting treatments, inevitably causing environmental pollution and environmental issues such as waste acid disposal in subsequent processing, which inevitably increases processing costs for users. There is an urgent need to develop a low-density steel that combines good performance, low density, and environmental friendliness to achieve the "green and lightweight" development goals for automotive steel. A search of relevant patents reveals the following similar patents:

[0004] CN 113025794 B discloses a method for improving the strength of Fe-Mn-Al-C low-density steel. The chemical composition, by weight percentage, is: C: 0.8%–1.6%, Mn: 15%–30%, Al: 5%–10%, Cr≤5%, Mo≤3%, Nb≤0.2%, Ti≤0.5%, Si≤2%, B≤0.6%, with the remainder being Fe and unavoidable impurities. The smelted billet is then rolled (with a rolling reduction of 40%–60%) or forged, followed by solution treatment at a temperature of 950℃–1100℃ for a holding time of 1h–3h. The patent adds a large amount of elements such as C, Mn, Cr, Mo, Si, Nb, Ti, and B, which is not conducive to obtaining good welding performance and significantly increases costs. Although the products produced under the guidance of the patent have extremely high strength, their plasticity is low (A value of 8-27%), which is not conducive to the forming of parts. In addition, the application does not take into account the control method of iron oxide scale, which is not conducive to reducing the pickling process and thus reducing the environmental impact.

[0005] CN 113046644 B discloses a 980MPa grade lightweight high-strength steel and its preparation method. Its chemical composition by weight percentage is: C: 0.21%~0.41%, Si: 0.8%~1.4%, Mn: 1.4%~2.5%, P: 0.04%~0.07%, S≤0.03%, Al: 3.1%~5.1%, Ti: 0.04%~0.21%, V: 0.03%~0.2%, Bi: 0.06%~0.18%, with the balance being Fe and unavoidable impurities, and satisfying 1.0≤(13C+2Mn) / (1.1Al+1.3Si)≤1.3, and the balance being Fe and unavoidable impurity elements. The billet heating temperature is 1210–1250℃, the initial rolling temperature is 1010–1160℃, the final rolling temperature is 860–940℃, the laminar cooling rate is >22℃ / s (22–57.2℃ / s), and the coiling temperature is <245℃; the annealing temperature is 810–890℃, the annealing holding time is 110–270s, the cooling rate is 22–64℃ / s, the aging treatment is 340–440℃, the aging time is 280–780s, and finally the temperature is cooled to room temperature at 12–32℃ / s. In this application, the Si content easily leads to surface quality deterioration, P strengthening (0.04%–0.07%) increases material brittleness, the yield of rare earth element Bi is uncontrollable, and the Ti content range is wide (0.04%–0.21%). When the Ti content is high, the liquid-precipitated TiN state severely impairs the material's ductility and toughness.

[0006] CN 115216704 B discloses a short-process production method for low-density steel based on thin strip continuous casting, wherein the chemical composition by weight percentage is: C: 0.60-1.50%, Mn: 16.00-25.00%, Al: 6.00-12.00%, V: 0.01-0.20%, Nb: 0.01-0.2%, with the remainder being Fe and unavoidable impurities. The molten steel, having passed smelting, is conveyed to a pair of relatively rotating casting rolls. The steel cools and solidifies on the casting surfaces of the rolls, then flows downwards through the gap between the rolls to form a thin strip. This thin strip is then hot-rolled in one pass to form a thin steel strip at a temperature of 850℃–1050℃. The hot-rolled strip is then cooled to 600℃–800℃ and coiled into a coil. The coiled strip undergoes a solution treatment at 900℃–1150℃ for approximately 1–3 hours. After solution treatment, the strip undergoes a cold rolling process with a reduction of 20–50%, followed by an aging treatment at 650℃–850℃ for approximately 10–12 hours, and then air-cooled. The high C and Mn content of this process is detrimental to achieving good weldability and increases alloy costs. Furthermore, the specialized equipment used in the twin-roll thin strip continuous casting process hinders the widespread adoption of this technology. Furthermore, the application did not consider methods for controlling iron oxide scale, thus failing to achieve the goals of acid-free washing and reducing environmental damage. Summary of the Invention

[0007] To address the aforementioned problems, a first aspect of the present invention provides a 980MPa grade low-density steel with the following chemical composition by weight percentage: C: 0.20%–0.45%, Si: 0.10–0.35%, Mn: 4.8%–7.2%, P≤0.015%, S≤0.008%, Al: 4.5%–5.5%, Nb: 0.015–0.035%, V: 0.030–0.070%, Ti: 0.015–0.065%, N≤0.004%, with the remainder being Fe and unavoidable impurities.

[0008] Further, its chemical composition by weight percentage is as follows: C: 0.30–0.42%, Si: 0.15–0.30%, Mn: 5.5–6.8%, Al: 4.8–5.2%, P≤0.012%, S≤0.005%, Nb: 0.020–0.030%, V: 0.040–0.060%, Ti: 0.030–0.055%, N≤0.0030%, with the balance being Fe and unavoidable impurities.

[0009] Furthermore, the yield strength is 580–800 MPa, the tensile strength is 992–1056 MPa, and the elongation A is… 50The value is 26.0%–32.5%; the microstructure consists of 16%–21% high-temperature ferrite, 10%–14% critical ferrite, 49%–59% lath martensite and 12%–16% retained austenite; the iron oxide scale consists of 85%–90% Fe3O4, 8%–12% Fe, a small amount of dispersed FeO and trace amounts of Fe2O3.

[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned 980MPa grade low-density steel, comprising:

[0011] Smelting: Smelting is carried out according to the above chemical composition;

[0012] Hot rolling: includes rough rolling and finish rolling; rough rolling is performed above the recrystallization temperature to obtain an intermediate billet with iron oxide scale removed, and finish rolling is performed below the recrystallization temperature to control the thickness and composition of iron oxide scale and obtain hot-rolled coils of the target thickness size.

[0013] The bell-type annealing is carried out in a reducing atmosphere to achieve the reverse transformation of martensite to austenite and improve the forming performance of the oxide layer.

[0014] Furthermore, in the rough rolling process, the slab obtained from smelting is heated, and the slab after exiting the furnace is pre-cooled. A 3+3 rough rolling mode is adopted, with the reduction of the first three passes ≥16% and the reduction of the last three passes ≥14%. The thickness of the intermediate slab is 30±2mm. The first, third, fourth and sixth passes are descaling, with a descaling water pressure ≥22MPa and a descaling temperature ≥1180℃.

[0015] The finishing rolling adopts a seven-pass speed-increasing rolling mode, with an initial rolling temperature of 940-990℃ and a final rolling temperature of 840-880℃. The speed of the first pass is ≥1.5m / s, and the rolling speed of each subsequent pass gradually increases until the speed of the last pass is ≥6.8m / s, and the reduction rate of the last pass is ≤13%.

[0016] Furthermore, the slab obtained from smelting is heated slowly to 1250±20℃ and held at that temperature for 3 hours before being removed from the furnace, with the furnace time being 4.5 to 7 hours.

[0017] Furthermore, the thickness of the iron oxide scale controlled by the finishing rolling for the seven passes is as follows: ≤1.8μm, ≤2.6μm, ≤3.3μm, ≤4.1μm, ≤4.8μm, ≤5.4μm and ≤6.0μm.

[0018] Furthermore, the hot rolling also includes laminar flow cooling. After finishing rolling, the laminar flow cooling first involves rapid cooling with the manifold fully open, followed by sparse cooling with the manifold. Vertical water is turned on at the end of the laminar flow cooling process, and the thickness of the iron oxide scale after laminar flow cooling is controlled within 7.8 μm.

[0019] Furthermore, the hot rolling also includes cooling and then coiling, wherein the coiling temperature is <245℃, and an iron oxide scale mainly composed of Fe3O4 is obtained with a thickness ≤9.2μm.

[0020] Furthermore, the bell-type annealing is as follows: the hot-rolled coil is placed in a bell-type annealing furnace, and H2 reduction is used to slowly heat the strip to 630-670°C at a rate of 2-5°C / min, hold it at that temperature for 7-10 hours, and then cool it to room temperature with the furnace.

[0021] The 980MPa grade low-density steel provided by this invention reduces the density of the steel by adding the lightweight element Al, appropriately increases the Mn content to mitigate the adverse effects of Al addition on the shrinkage of the austenite phase region, and utilizes microalloying elements (Nb, V, Ti) to refine the grains and improve the product's strength and plasticity through precipitation. The preparation method utilizes a bell-type annealing furnace to perform a reverse phase transformation from martensite to austenite, improving the stamping effect; and by controlling the hot rolling and bell-type annealing processes, a thinner and denser oxide layer is obtained, avoiding environmental pollution caused by pickling, shot blasting, and other treatments. This invention requires low equipment investment and is highly operable, providing technical support for the development of pickling-free 980MPa grade low-density high-strength steel. Attached Figure Description

[0022] Figure 1 Metallographic photograph of a pickling-free low-density steel provided in an embodiment of this application.

[0023] Figure 2 A scanning electron microscope image of a pickling-free low-density steel provided in an embodiment of this application.

[0024] Figure 3 The XRD test results of a pickling-free low-density steel provided in this application embodiment. Detailed Implementation

[0025] In a first aspect, the present invention provides a 980MPa grade low-density steel with the following chemical composition by weight percentage: C: 0.20%–0.45%, Si: 0.10–0.35%, Mn: 4.8%–7.2%, P≤0.015%, S≤0.008%, Al: 4.5%–5.5%, Nb: 0.015–0.035%, V: 0.030–0.070%, Ti: 0.015–0.065%, N≤0.004%, with the remainder being Fe and unavoidable impurities.

[0026] The 980MPa grade low-density steel provided in this embodiment of the invention reduces the density of steel by adding the light element Al, appropriately increases the content of Mn element to reduce the adverse effect of the shrinkage of the austenite phase region caused by the addition of Al element, and improves the strength and plasticity of the product by using microalloying elements (Nb, V, Ti) to refine the grains and precipitate.

[0027] In some embodiments, the chemical composition, by weight percentage, is: C: 0.30–0.42%, Si: 0.15–0.30%, Mn: 5.5–6.8%, Al: 4.8–5.2%, P≤0.012%, S≤0.005%, Nb: 0.020–0.030%, V: 0.040–0.060%, Ti: 0.030–0.055%, N≤0.0030%, with the balance being Fe and unavoidable impurities.

[0028] Specifically, as a preferred option, the contents of C, Si, Mn, and Al satisfy the above conditions to ensure the intensity of content control of austenite and martensite, because Al, as a ferrite-forming element, greatly reduces the austenite phase region, Si affects the formation of carbides, while C and Mn, as austenite-forming elements, expand the austenite phase region; the contents of Nb, V, and Ti satisfy the above conditions to ensure that the content of the second phase plays a role in precipitation and grain refinement.

[0029] In some embodiments, the yield strength of the 980MPa grade low-density steel is 580–800MPa, the tensile strength is 992–1056MPa, and the elongation A is [missing information]. 50 The value is 26.0%–32.5%; the microstructure consists of 16%–21% high-temperature ferrite, 10%–14% critical ferrite, 49%–59% lath martensite and 12%–16% retained austenite; the iron oxide scale consists of 85%–90% Fe3O4, 8%–12% Fe, a small amount of dispersed FeO and trace amounts of Fe2O3.

[0030] Carbon: C is an important austenitic element in steel, capable of stabilizing austenite structure, increasing stacking fault energy, and inducing dynamic strain aging. It is particularly important in high-Al content, low-density steels (Fe...). Mn Al C plays a role in balancing the volume fraction of ferrite and austenite phases in the alloy system. Through heat treatment, C is enriched in the austenite phase of the steel, forming a metastable austenite phase, thereby improving the formability and elongation of the steel sheet. Too low a C content will cause instability in the austenite structure, leading to a decrease in the strength and toughness of the low-density steel. Simultaneously, C can react with microalloying elements in the steel to form nanoscale carbides, and together with Mn and Al elements, form κ-carbides ((Fe,Mn)3AlC). The combined effect of these two elements produces precipitation strengthening, increasing the strength of the steel. However, excessively high C content will promote the formation of coarse κ-carbides at the austenite grain boundaries, impairing the elongation of the low-density steel. Therefore, the C content in this invention is 0.20%–0.45%, preferably 0.30%–0.42%.

[0031] Silicon (Si): Si is commonly used as a deoxidizer in steel. Similar to Al, Si reduces the specific gravity of steel and increases its strength and stacking fault energy, but it reduces the dynamic strain aging of steel and deteriorates its weldability. Si can dissolve in ferrite and austenite to increase the strength of steel, and its effect is second only to C and P, and stronger than elements such as Mn, Cr, Ti, and Ni. Si can also inhibit the precipitation of carbides in ferrite, allowing dissolved C atoms to fully enrich into austenite, thereby improving its stability. Too low a Si content makes it difficult to obtain retained austenite at room temperature. However, when the Si content is too high, the surface iron oxide scale formed by Si in the heating furnace is difficult to remove, increasing the difficulty of descaling and resulting in a poor surface finish. Therefore, the Si content of this invention is 0.10–0.35%, preferably 0.15–0.30%.

[0032] Manganese (Mn) plays a role in solid solution strengthening and austenite stabilization in steel. On the one hand, Mn enhances the strength of steel plates through solid solution strengthening; on the other hand, it stabilizes austenite, promoting the formation of retained austenite phase and improving the plasticity of the steel plate. Furthermore, Mn increases the stacking fault energy of steel, inhibits martensitic transformation, induces dense twinning during deformation, and effectively increases the elongation of the steel. Low Mn content tends to result in insufficient austenite content and poor stability, which is detrimental to achieving good plasticity. Conversely, excessively high Mn content leads to banded structures in the steel, reducing the toughness of the plate; it also makes the austenite too stable, making it difficult to transform into martensite during deformation, thus reducing the formability of the steel plate. Therefore, in this invention, the Mn content is 4.8%–7.2%, preferably 5.5%–6.8%.

[0033] Aluminum: The density of Al is 2.7 g / cm³. 3 It is much lower than the density of Fe (7.85 g / cm³). 3 Al content can significantly reduce material density. A certain Al content can also significantly improve the hot deformation resistance and corrosion resistance of steel, delay dynamic cracking, and significantly increase the stacking fault energy of steel, altering the deformation mechanism. Medium-manganese steel containing Al can provide some buffering effect during violent impacts. Al is a strong ferritinizing element; excessively high Al content easily promotes the formation of the ferrite phase and reduces the austenite phase content. Furthermore, Al reacts with C and Mn elements to form κ-carbides ((Fe,Mn)3AlC), producing precipitation strengthening and increasing the strength of the steel, but significantly reducing the plasticity of low-density steel. Too low an Al content will not reduce material density, while too high an Al content is detrimental to obtaining good plasticity. Therefore, the Al content in this invention is 4.5%–5.5%, preferably 4.8%–5.2%.

[0034] Niobium (Nb) effectively delays the recrystallization of deformed austenite, inhibits austenite grain growth, and increases the austenite recrystallization temperature. Simultaneously, Nb combines with C and N to form Nb(C,N), which effectively suppresses grain coarsening during hot working, thereby refining the grains and increasing the strength of the steel plate. When the steel is heated to 800–1300°C, Nb will solidify in the austenite. Excessive Nb cannot be dissolved into the matrix and will increase the alloy cost. In this invention, the Nb content is 0.015%–0.035%, preferably 0.020%–0.030%.

[0035] Vanadium (V) acts as a grain refiner and precipitation strengthener in steel by forming carbonitrides. The high solubility of V (C, N) in austenite allows for lower reheating temperatures, resulting in lower production costs. The deformation mechanism of the steel in this invention is primarily dislocation slip. The addition of V can precipitate fine precipitates in the steel. These precipitates can, on the one hand, increase the nucleation rate and hinder grain growth to refine the grains; on the other hand, they can hinder dislocation movement to increase strength, ultimately resulting in good overall mechanical properties. Therefore, the V content is set in the range of 0.030–0.070% by mass, preferably 0.040–0.060%.

[0036] Titanium (Ti): Ti is a highly reactive element that readily combines with oxygen (O). During smelting, some Ti acts as a deoxidizer. At high temperatures, Ti forms TiN, inhibiting the formation of AlN inclusions in steel. At medium temperatures, TiC precipitation effectively inhibits the precipitation of phosgene carbides, thereby improving the ductility and yield strength of the steel. However, adding a large amount of Ti can clog the continuous casting nozzle or cause inclusion defects due to excessive TiN crystallization. Furthermore, excessively high Ti content can significantly reduce the diffusion rate of carbon (C) in austenite, decreasing the C content in austenite, leading to decreased matrix stability and reduced plasticity. Therefore, the Ti content, expressed as a mass percentage, is set within the range of 0.015–0.065%, preferably 0.030–0.055%.

[0037] Phosphorus: In steel, phosphorus (P) is generally dissolved in ferrite and has a strong solid solution strengthening effect. However, during the solidification of the slab, phosphorus (P) segregates along columnar or equiaxed grain boundaries, making the slab brittle at both high and room temperatures and potentially causing cracks. Furthermore, after processing, P increases the ductility-brittle transition temperature of steel and makes it more susceptible to hydrogen embrittlement. Therefore, the P content, expressed as a percentage by mass, is preferably ≤0.015%, and more preferably ≤0.012%.

[0038] Sulfur: S is an impurity element in steel, which tends to segregate at grain boundaries and forms low-melting-point FeS with Fe in the steel, reducing the toughness of the steel. In addition, S can also form inclusions such as MnS, which can cause cracking when the steel is hot-rolled or cold-rolled. Therefore, the S content is set in the range of ≤0.008% by mass, preferably ≤0.005%.

[0039] Nitrogen: N is an impurity element in steel. During solidification, hot rolling, and annealing after cold rolling, N readily reacts with Ti, Al, and Nb in the steel to form TiN, AlN, and NbN. TiN and AlN present in molten steel pose a risk of inclusion defects, and large amounts of TiN and AlN can promote crack formation in cast slabs. Liquid-precipitated TiN significantly deteriorates the plasticity and toughness of steel. Therefore, the sulfur (S) content, expressed as a percentage by mass, is set within the range of ≤0.005%, preferably ≤0.003%.

[0040] In a second aspect, the present invention provides a method for preparing the above-mentioned 980MPa grade low-density steel, comprising:

[0041] Smelting: Smelting is carried out according to the above chemical composition;

[0042] Hot rolling: includes rough rolling and finish rolling; rough rolling is performed above the recrystallization temperature to obtain an intermediate billet with iron oxide scale removed, and finish rolling is performed below the recrystallization temperature to control the thickness and composition of iron oxide scale and obtain hot-rolled coils of the target thickness size.

[0043] The bell-type annealing is carried out in a reducing atmosphere to achieve the reverse transformation of martensite to austenite and improve the forming performance of the oxide layer.

[0044] Specifically, after smelting, slabs with the aforementioned chemical composition are obtained through casting; the slabs are rough rolled above the recrystallization temperature to obtain intermediate slabs with iron oxide scale removed; then, the intermediate slabs are finish rolled below the recrystallization temperature to obtain hot-rolled coils; finally, a bell-type annealing furnace is used to perform a reverse phase transformation from martensite to austenite to improve the stamping effect; by controlling the hot rolling and bell-type annealing processes, a thinner and denser oxide layer is obtained, avoiding environmental pollution caused by pickling, shot blasting, and other treatments. The equipment investment is low and the operation is highly operable, providing technical support for the development of pickling-free 980MPa grade low-density high-strength steel.

[0045] In some embodiments, the rough rolling process involves heating the slab obtained from smelting, pre-cooling the slab after it exits the furnace, and using a 3+3 rough rolling mode. The reduction in the first three passes is ≥16%, and the reduction in the last three passes is ≥14%. The thickness of the intermediate slab is 30±2mm. Descaling is performed in the first, third, fourth, and sixth passes, with a descaling water pressure ≥22MPa and a descaling temperature ≥1180℃. The finish rolling process uses a seven-pass speed-increasing rolling mode. The initial rolling temperature is 940~990℃, and the final rolling temperature is 840~880℃. The speed of the first pass is ≥1.5m / s, and the rolling speed of each subsequent pass gradually increases until the speed of the last pass is ≥6.8m / s, with a reduction rate of ≤13% in the last pass.

[0046] Specifically, the large deformation of rough rolling is beneficial for rapidly compressing the thickness of the slab, while the larger amount of descaling water ensures that the iron oxide scale formed during the heating process is not completely removed. Finish rolling, on the other hand, processes the intermediate slab to the desired thickness and accumulates a large amount of deformation to refine the grains during cooling. The first, third, fourth, and sixth descaling passes have a descaling water pressure ≥22MPa; the descaling temperature of the steel billet is ≥1180℃, completely removing the hard and brittle low-melting-point FeO·Fe2SiO4 formed during heating. After rough rolling, the iron oxide scale is mainly FeO with a thickness ≤1.0μm. The iron oxide scale formed during rough rolling is mainly FeO with a small amount of Fe3O4 and trace amounts of Fe2O3, resulting in a thinner iron oxide scale thickness. The initial rolling temperature of the finishing mill is 940–990℃, and the final rolling temperature is 840–880℃. The speed-increasing rolling mode is adopted to reduce the time in the high-temperature zone of the strip, thereby reducing the oxide layer thickness. The finishing mill adopts a seven-pass rolling mode and lubrication rolling. The medium-pressure water between each pass of the finishing mill is turned on to reduce the strip temperature. The exit speed of the finishing mill in the last pass is ≥6.8m / s to obtain a thinner iron oxide scale thickness. The reduction rate of the last pass is ≤13% to avoid the breakage of FeO formed during the finishing mill process.

[0047] In some embodiments, the slab obtained by smelting is heated slowly to 1250±20°C and held at that temperature for 3 hours before being removed from the furnace, with the furnace time being 4.5 to 7 hours.

[0048] Specifically, if the time spent in the furnace exceeds 7 hours, the steel will be returned to the furnace for reheating and reclassified as another type of steel to avoid excessive iron oxide scale.

[0049] In some embodiments, the thickness of the iron oxide scale controlled by the finishing rolling seven passes is, in sequence: ≤1.8μm, ≤2.6μm, ≤3.3μm, ≤4.1μm, ≤4.8μm, ≤5.4μm and ≤6.0μm.

[0050] Specifically, by controlling the thickness of the iron oxide scale in each pass of the finishing rolling process, the effect of eliminating the need for acid washing was ensured.

[0051] In some embodiments, the hot rolling further includes laminar flow cooling. After finishing rolling, the laminar flow cooling first involves rapid cooling with the manifold fully open, followed by sparse cooling with the manifold. Vertical water is turned on at the end of the laminar flow cooling process, and the thickness of the iron oxide scale after laminar flow cooling is controlled within 7.8 μm.

[0052] Specifically, the first four sets of manifolds for laminar flow cooling after steel strip rolling are fully opened for rapid cooling, which quickly reduces the temperature and avoids excessive heat that would lead to thicker iron oxide scale. The subsequent manifolds adopt a sparse cooling mode of opening one every other manifold to ensure uniform iron oxide scale thickness. At the end of the laminar flow cooling, vertical water blowing is turned on to avoid poor plate shape and iron oxide scale thickness caused by water accumulation. After laminar flow cooling, the thickness of iron oxide scale is controlled within 7.8μm, and the iron oxide scale composition is approximately 30% FeO + approximately 70% Fe3O4 + a small amount of Fe2O3.

[0053] In some embodiments, the hot rolling further includes cooling and then coiling, wherein the coiling temperature is <245℃, and an iron oxide scale mainly composed of Fe3O4 with a thickness ≤9.2μm is obtained.

[0054] Specifically, the winding temperature is <245℃ to obtain an iron oxide scale mainly composed of Fe3O4 with a thickness ≤9.2μm, while avoiding the adverse effects of coarse κ-carbides on plasticity.

[0055] In some embodiments, the bell-type annealing is performed by placing the hot-rolled coil in a bell-type annealing furnace, using H2 reduction, slowly heating the strip to 630-670°C at a rate of 2-5°C / min, holding it at that temperature for 7-10 hours, and then cooling it to room temperature in the furnace.

[0056] Specifically, the hot-rolled coil, produced using a tight-coil method, is placed in a bell-type annealing furnace (using H2 reduction). The strip is slowly heated to 630–670°C at a rate of 2–5°C / min, held at that temperature for 7–10 hours, and then cooled to room temperature in the furnace. This process achieves the reverse transformation of martensite to austenite, and also allows Fe to be deposited in an oxygen-deficient environment. 2+ Ions continuously diffuse from the steel substrate into the oxide layer, transforming Fe2O3 into Fe3O4, ultimately forming an iron oxide scale with a thickness ≤9.8μm, consisting of (85%–90%) Fe3O4 + (8–12%) Fe (including α-Fe and δ-Fe) + a small amount of dispersed FeO + trace amounts of Fe2O3, thus improving the forming performance of the oxide layer.

[0057] Example 1: A 980MPa grade low-density steel and its preparation method

[0058] This embodiment provides three groups of acid-free 980MPa grade low-density high-strength steels, whose chemical composition is shown in Table 1.

[0059] Table 1. Chemical composition (wt.%) of pickling-free 980MPa grade low-density high-strength steel

[0060]

[0061]

[0062] The specific process for preparing the above-mentioned pickling-free 980MPa grade low-density high-strength steel is as follows:

[0063] A. Smelting process: Through smelting process, slabs of 980MPa grade low-density high-strength steel without pickling are prepared as shown in Table 1.

[0064] B. Hot rolling process: The slab is slowly heated to 1250±20℃ and held for 3 hours before being taken out of the furnace (furnace time ≥4.5h; if furnace time exceeds 7 hours, it is returned to the furnace to avoid excessive iron oxide scale). The roughing mill is fed with soft blowing water to pre-cool the iron scale. The two roughing mills adopt a 3+3 roughing mode. The reduction of the first three passes is ≥16%, and the reduction of the last three passes is ≥14%. The first, third, fourth and sixth passes are descaling, and the descaling water pressure is ≥22MPa. The descaling temperature of the steel billet is ≥1180℃ to completely remove the hard and brittle low melting point FeO·Fe2SiO4 formed during the heating process. After roughing, the iron oxide scale is mainly FeO and its thickness is ≤1.0μm. The initial rolling temperature of the finishing mill is 940–990℃. A speed-increasing rolling mode is used to reduce the time spent in the high-temperature zone of the strip, thereby reducing the oxide layer thickness. The finishing mill employs a seven-pass rolling mode with lubrication. Medium-pressure water is turned on between each pass to lower the strip temperature. The speed of the first pass is ≥1.5 m / s, and the oxide scale thickness is controlled within 1.8 μm. The rolling speed of subsequent passes gradually increases, and the exit speed of the final pass is ≥6.8 m / s. The oxide scale thicknesses are ≤2.6 μm, ≤3.3 μm, ≤4.1 μm, and so on. For thicknesses of ≤4.8μm, ≤5.4μm, and ≤6.0μm, the iron oxide scale formed during rough rolling is mainly FeO, with a small amount of Fe3O4 and trace amounts of Fe2O3, to obtain a thinner iron oxide scale thickness. The final rolling temperature is 840~880℃, and the exit speed of the last rolling mill is ≥6.8m / s, to obtain a thinner iron oxide scale thickness. The reduction rate of the last pass is ≤13% to avoid the breakage of FeO formed during the finishing rolling process and to avoid excessive internal stress in the oxide layer, which could lead to excessive cracks and affect the forming performance of the oxide layer. The rapid cooling manifold after laminar flow of the steel strip after rolling is fully open, which quickly reduces the temperature and avoids excessive heat and thickening of the iron oxide scale. The subsequent manifold adopts a sparse cooling mode of opening one manifold every other manifold to ensure uniform iron oxide scale thickness. Vertical water blowing is turned on at the end of laminar cooling to avoid poor strip shape and iron oxide scale thickening caused by water accumulation. The thickness of the iron oxide scale after laminar cooling is controlled within 7.8μm. The iron oxide scale composition is about 30% FeO + about 70% Fe3O4 + a small amount of Fe2O3. The coiling temperature is <245℃ to obtain iron oxide scale mainly composed of Fe3O4 with a thickness ≤9.2μm. At the same time, it avoids the formation of coarse κ-carbides that would have an adverse effect on plasticity. The specific hot rolling process parameters are shown in Table 2.

[0065] Table 2 Main process parameters for hot rolling of pickled-free 980MPa grade low-density high-strength steel

[0066]

[0067] C. Bell-type annealing: The hot-rolled coil, manufactured using a tight-coil method, is placed in a bell-type annealing furnace (using H2 reduction). The strip is slowly heated to 630–670°C at a rate of 2–5°C / min, held at that temperature for 7–10 hours, and then cooled to room temperature in the furnace. This process achieves the reverse transformation of martensite to austenite and, in an oxygen-deficient environment, the Fe... 2+ Ions continuously diffuse from the steel substrate into the oxide layer, where Fe2O3 is converted into Fe3O4, ultimately forming an iron oxide scale with a thickness ≤9.8μm, consisting of (85%–90%) Fe3O4 + (8–12%) Fe (including α-Fe and δ-Fe) + a small amount of dispersed FeO + trace amounts of Fe2O3, thus improving the forming performance of the oxide layer. The parameters are shown in Table 3.

[0068] Table 3 Main process parameters for acid-free pickling grade 980MPa low-density high-strength steel

[0069]

[0070] The microstructure of the prepared Case 1 (No. 1) 980MPa grade low-density high-strength steel without pickling is as follows: Figure 1 As shown in Table 4, the mechanical properties of the above-mentioned acid-free 980MPa grade low-density high-strength steel were tested according to GB / T228-2010 "Metallic Materials - Tensile Testing at Room Temperature".

[0071] Table 4 Mechanical Properties of Acid-Free 980MPa Grade Low-Density High-Strength Steel

[0072]

[0073] The characterization of the 980MPa grade low-density steel in Example 1 of this embodiment is shown in [link to example]. Figures 1-3 , Figure 1 This is a metallographic photograph, magnified at a low level, which allows us to see the overall structure and proportions. Figure 2 for Figure 1 The magnified view shows the shape, size, and size of each phase of the steel. According to... Figure 3 The XRD pattern can be used to determine the content of retained austenite.

[0074] It will be readily understood by those skilled in the art that the above-described advantageous methods can be freely combined and superimposed without conflict. The above are merely preferred embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application. The above are merely preferred embodiments of this application. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of this application, and these improvements and modifications should also be considered within the protection scope of this application.

Claims

1. A 980MPa grade low-density steel, characterized in that, The chemical composition by weight percentage is as follows: C: 0.20%~0.45%, Si: 0.10~0.35%, Mn: 4.8%~7.2%, P≤0.015%, S≤0.008%, Al: 4.5%~5.5%, Nb: 0.015~0.035%, V: 0.030~0.070%, Ti: 0.015~0.065%, N≤0.004%, with the remainder being Fe and unavoidable impurities; the iron oxide scale thickness of the 980MPa grade low-density steel is ≤9.8μm, and the iron oxide scale is composed of 85%~90%Fe3O4, 8~12%Fe, a small amount of dispersed FeO and trace amounts of Fe2O3.

2. The 980MPa grade low-density steel as described in claim 1, characterized in that, The chemical composition by weight percentage is as follows: C: 0.30~0.42%, Si: 0.15~0.30%, Mn: 5.5~6.8%, Al: 4.8~5.2%, P≤0.012%, S≤0.005%, Nb: 0.020~0.030%, V: 0.040~0.060%, Ti: 0.030~0.055%, N≤0.0030%, with the balance being Fe and unavoidable impurities.

3. The 980MPa grade low-density steel as described in claim 1 or 2, characterized in that, Yield strength is 580~800MPa, tensile strength is 992~1056MPa, and elongation is A 50 The value is 26.0~32.5%; the microstructure includes 16%~21% high-temperature ferrite, 10%~14% critical ferrite, 49%~59% lath martensite and 12%~16% retained austenite.

4. The method for preparing 980MPa grade low-density steel according to any one of claims 1 to 3, characterized in that, include: Smelting: Smelting according to the chemical composition described in claim 1; Hot rolling includes roughing and finishing rolling; roughing is performed above the recrystallization temperature to obtain an intermediate billet with iron oxide scale removed, and finishing rolling is performed below the recrystallization temperature to control the thickness and composition of the iron oxide scale and obtain a hot-rolled coil of the target thickness; wherein, the finishing rolling adopts a seven-pass speed-increasing rolling mode, and the iron oxide scale thickness of the seven passes is controlled as follows: ≤1.8μm, ≤2.6μm, ≤3.3μm, ≤4.1μm, ≤4.8μm, ≤5.4μm and ≤6.0μm; after finishing rolling, laminar flow cooling is performed, and the iron oxide scale thickness is controlled within 7.8μm; after cooling, it is coiled to obtain an iron oxide scale mainly composed of Fe3O4 with a thickness ≤9.2μm; The bell-type annealing is carried out in a reducing atmosphere to achieve the reverse transformation of martensite to austenite and improve the forming performance of the oxide layer, ultimately forming an iron oxide scale with a thickness of ≤9.8μm, consisting of 85%~90% Fe3O4, 8~12% Fe, a small amount of dispersed FeO, and trace amounts of Fe2O3.

5. The method for preparing 980MPa grade low-density steel as described in claim 4, characterized in that, The rough rolling process involves heating the slab obtained from smelting, pre-cooling the slab after it exits the furnace, and using a 3+3 rough rolling mode. The reduction in the first three passes is ≥16%, and the reduction in the last three passes is ≥14%. The thickness of the intermediate slab is 30±2mm. The first, third, fourth, and sixth passes are used for descaling, with a descaling water pressure ≥22MPa and a descaling temperature ≥1180℃. The finishing rolling process has an initial rolling temperature of 940~990℃ and a final rolling temperature of 840~880℃. The speed of the first pass is ≥1.5m / s, and the rolling speed of each subsequent pass gradually increases until the speed of the last pass is ≥6.8m / s. The reduction rate of the last pass is ≤13%.

6. The method for preparing 980MPa grade low-density steel as described in claim 5, characterized in that, The slab obtained from smelting is heated slowly to 1250±20℃ and held at that temperature for 3 hours before being taken out of the furnace. The furnace time is 4.5~7 hours.

7. The method for preparing 980MPa grade low-density steel as described in claim 4, characterized in that, The laminar flow cooling after finishing rolling first involves rapid cooling with the manifold fully open, followed by sparse cooling with the manifold sparsely open, and then vertical purging water is activated at the end of the laminar flow cooling process.

8. The method for preparing 980MPa grade low-density steel as described in claim 4, characterized in that, The hot rolling also includes cooling and then coiling, wherein the coiling temperature is <245℃.

9. The method for preparing 980MPa grade low-density steel as described in claim 4, characterized in that, The bell-type annealing process involves placing the hot-rolled coil in a bell-type annealing furnace, using H2 reduction, and slowly heating the strip to 630-670°C at a rate of 2-5°C / min, holding it at that temperature for 7-10 hours, and then cooling it to room temperature with the furnace.

Citation Information

Patent Citations

  • A method for improving the strength of Fe-Mn-Al-C low-density steel

    CN113025794B

  • A 980MPa grade lightweight high-strength steel and its preparation method

    CN113046644B

  • A Short-Process Production Method for Low-Density Steel Based on Thin Strip Continuous Casting

    CN115216704B

  • Ferrite low-density high-strength steel and manufacturing method thereof

    CN104928568A

  • 850MPa-grade environment-friendly pickling-free low-density high-strength steel and preparation method thereof

    CN116949357A